1999
DOI: 10.1021/ma980433a
|View full text |Cite
|
Sign up to set email alerts
|

Change of Elastic Modulus of Strongly Charged Hydrogels at the Collapse Transition

Abstract: The swelling and mechanical behavior of polyelectrolyte gels with the degree of ionization varying from 7 to 100 mol % were studied in mixtures of a good solvent and a poor solvent. In a good solvent region for weakly charged gels the shear modulus decreases with the gel swelling, while for strongly charged gels swelling leads to the increase of the shear modulus. Also for strongly charged gels the elastic modulus can remain unchanged during the volume phase transition (for a weakly charged gel, a jump in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 12 publications
4
18
0
Order By: Relevance
“…That is, the charge density dependence of the collapse region was most significant for alcohols and hardly observed for AcN systems. A similar result was found by Zaroslov et al21 for an anionic gel having sulfonate groups in aqueous EtOH; the transition region (EtOH concentration) slightly shifted to a lower concentration as the charge density increased from 80 to 100%. The authors ascribed the shift to an enhanced number of the bound counterions available for the aggregation of the charged groups with increasing charge density.…”
Section: Resultssupporting
confidence: 88%
“…That is, the charge density dependence of the collapse region was most significant for alcohols and hardly observed for AcN systems. A similar result was found by Zaroslov et al21 for an anionic gel having sulfonate groups in aqueous EtOH; the transition region (EtOH concentration) slightly shifted to a lower concentration as the charge density increased from 80 to 100%. The authors ascribed the shift to an enhanced number of the bound counterions available for the aggregation of the charged groups with increasing charge density.…”
Section: Resultssupporting
confidence: 88%
“…Figure 6 shows the experimental stress-deformation ratio curve of the as-prepared tetra-PEG gel (Q=1) and the theoretical curve predicted using Eq. (24). The stresses were normalized by their Young's moduli E. For comparison, the curve calculated with the neo-Hookean (NH) model , ( 2 5 ) is also shown 49 .…”
Section: Comparison With the Elasticity Modelsmentioning
confidence: 99%
“…Uniaxial normalized stress-deformation ratio curves of the as-prepared tetra-PEG gel determined via an experiment and calculated using the WLC model (Eqs. (19,21,24)). The curve calculated based on NH model (Eq.…”
Section: Comparison With the Elasticity Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…[37][38][39] Takigawa et al 40 observed that the elastic modulus of PNIPA gels in a collapsed state was much higher than that in a swollen state because of the formation of physical crosslinks at a high PNIPA net-work concentration. Zaroslov et al 41 published a article concerning the swelling and mechanical behavior of polyelectrolyte gels in mixtures of good and poor solvents. In a good solvent region for weakly charged gels, the shear modulus decreased with the gel swelling.…”
Section: Introductionmentioning
confidence: 99%